Aerodynamic analysis of a cyclist scale-model in dropped position (2020)
This document presents a study of a flow around a 1:2.5 cyclist scale-model in dropped position. In this study, the wind tunnel experiment of the model inside the test section was simulated by using two Reynolds Averaged Navier-Stokes (RANS) Turbulence Models, namely Spalart-Allmaras (SA) and Shear Stress Transport (SST)-k' in both steady and transient formulations. The commercial CFD code Fluent 18.2 is used for the simulations. This study focuses on examining field variables through comparative charts and contours to hypothesize flow characteristics causing high difference in estimated drag area between the two turbulence models studied (~30%). Force, Moment, Surface Pressure, and velocity measurements from both turbulent models would serve as predictors of the same variables of experimental measurements of the same model. The final aim is to be able assess prediction performance of both Turbulent models and discuss suitability to perform CFD cycling simulations by using each of the two models